Antibiofilm Activity and Synergistic Effects of Thymol-Loaded Poly (Lactic-Co-Glycolic Acid) Nanoparticles with Amikacin against Four Salmonella enterica Serovars - Christian Ramsès Kuaté Tokam; Borel Bisso Ndezo; Nathalie Boulens; Eric Allémann; Florence Delie; Jean Paul Dzoyem (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Salmonella species are frequently linked to biofilm-associated infections. Biofilm formation intensively reduces the efficacy of antibiotics and the host immune system. Therefore, new therapeutic strategies are needed. Thymol, the main monoterpene phenol found in Thymus vulgaris, has been shown to possess potent antibiofilm activity. Our previous findings showed that thymol enhanced the antibiofilm activity of aminoglycosides against Salmonella enterica serovars. However, the clinical potential of thymol has not yet been realized due to its low aqueous solubility and high volatility. Nano-based drug delivery systems have emerged as a novel strategy to resolve these problems. This study aimed to investigate the antibiofilm activity of thymol-loaded poly (lactic-co-glycolic acid) nanoparticles (TH-NPs) and their synergism when used in combination with amikacin antibiotics. Methods. The antibacterial activity of TH-NPs was evaluated using the broth microdilution method. Biofilm formation and antibiofilm assays were performed by the miniaturized microtiter plate method. Interaction studies between TH-NPs and amikacin against biofilm were determined using the checkerboard method. Results. TH-NPs exhibited antibacterial activity against planktonic cells of S. enterica serovars that were more efficient (8 to 32 times) than free thymol alone. S. Typhimurium and S. Choleraesuis isolates were considered strong biofilm producers. The combination of TH-NPs with amikacin showed synergistic activity in the inhibition and eradication of S. enterica serovar biofilm. The minimum biofilm inhibitory concentration (MBIC) and minimum biofilm eradication concentration (MBEC) of amikacin were reduced by 32 to 128-fold when used in combination with TH-NPs. Time-kill kinetic studies showed that the combination of TH-NPs with amikacin possesses bactericidal action. Conclusion. This study suggests that the combination of TH-NPs with amikacin can be an alternative to overcome biofilm-associatedSalmonella diseases and therefore should be further explored as a model to search for new antibiofilm drugs.